Constantin Carathéodory in Munich (1924–1945): moral courage and constraints under the Nazi Regime - Hans Josef Pesch (Central European Journal of Operations Research, 2025)
This paper examines the life and decisions of Constantin Carathéodory, a Greek-German mathematician, during his tenure at the University of Munich (1924–1945). It addresses criticisms of Carathéodory's actions during the Nazi regime, analyzing historical sources to argue that he maintained a hostile attitude toward the regime while supporting persecuted colleagues. The study highlights the constraints he faced and the moral choices he made against the backdrop of a tragic period in German history, offering a nuanced understanding of his legacy.
Keywords: 650; Constantin Carathéodory; Calculus of variation; Partial diffential equations; Thermodynamics; Maria Georgiadou; Ulf Hashagen